1994
DOI: 10.1021/bi00201a029
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Coupled Repair of Psoralen Cross-Links but Not Monoadducts in Chinese Hamster Ovary Cells

Abstract: We have examined the rate and extent of removal of 4'-(hydroxymethyl)-4,5',8-trimethylpsoralen (HMT) cross-linkable monoadducts and interstrand cross-links from restriction fragments within the amplicon containing the dihydrofolate reductase (DHFR) gene in the Chinese hamster ovary (CHO) cell line B11. The rate and extent of removal of HMT cross-links was significantly greater in an actively transcribed fragment than in a nontranscribed extragenic fragment of similar size. For the 5' half of the DHFR gene, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…In our study, both the CSA and the CSB mutant were significantly defective in the repair of MMC ICLs located in the actively transcribed region of the reporter substrate. These observations are consistent with the report that TCR is involved in the repair of psoralen cross-links in hamster cells (20). In our study, a profound strand bias toward the transcribed strand was found, whereas the loss of transcription completely abolished this effect.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, both the CSA and the CSB mutant were significantly defective in the repair of MMC ICLs located in the actively transcribed region of the reporter substrate. These observations are consistent with the report that TCR is involved in the repair of psoralen cross-links in hamster cells (20). In our study, a profound strand bias toward the transcribed strand was found, whereas the loss of transcription completely abolished this effect.…”
Section: Discussionsupporting
confidence: 94%
“…DNA adducts are preferentially removed from active genes by transcription-coupled repair (55). NER excises adducts more quickly from the transcribed strand than the non-transcribed strand (56), leading to more mutations on the non-transcribed strand.…”
Section: Discussionmentioning
confidence: 99%
“…Processing of ICL in mammalian cells appears to be mediated by similarly diverse mechanisms as well as transcription [12,13] and certain mismatch repair proteins [14], although the relative importance of differing pathways and the detailed sequence of events remain to be elucidated [1]. For example, the contribution of NER proteins to ICL repair is unclear.…”
Section: Introductionmentioning
confidence: 99%